Clinical Efficacy and Complications of Uterine Artery Embolization in Symptomatic Uterine Fibroids - Salehi, Mohammadgharib (Glob J Health Sci, 2016)
We decided to evaluate the efficacy and complications of uterine artery embolization (UAE) in patients with symptomatic uterine fibroids. Sixty-five premenopausal patients, without considering the fibroids size and its location, were treated by bilateral UAE. At baseline and after 3, 6, and 12 months MRI was obtained to determine the uterine length and fibroid diameter. In addition, symptoms of the patients were documented at these follow-up schedules. UAE was successful in 62 (95.4%) cases. Complete infarction rate of the fibroid was 83.1%. After 12 months, the uterine length showed a decrease of 55.7% (mean of 9.4 cm) and the diameter of the dominant fibroid revealed a decrease of 52.1% (mean of 3.4 cm). Menorrhagia improved in 45 cases (91.8%), abdominal mass in 24 cases (82.28%), urinary symptoms in 17 cases (85%), pelvic pain in 21 cases (84%), and dysmenorrhea in 25 cases (80.6%). At final follow-up performed after one year, complete infarction of the fibroma was demonstrated in 49 patients (83.1%). Two cases achieved successful pregnancy in the one year follow-up period. Five patients developed post-embolization syndrome which necessitated admission to the hospital. Twenty-two patients presented and complained of pain for which outpatient pain management was done. UAE was a successful treatment for uterine fibroids that preserved the uterus, had minimal complications, and required short hospitalization and recovery.